Analysis Of Metabolic Status Indicators In Children Depending On The Type Of Feeding - Prof. Bobomuratov Turdikul Akramovich; Sultanova Nafisa Sabirovna; Khudaybergenova Nasiba Pulat qizi; Khudaybergenova Luiza Pulatovna; Xo'janiyozova Maftuna Yusupboy qizi (Zien Journals, 2025)
The study investigates metabolic disorders in children depending on the type of feeding during the first years of life. Breastfed children demonstrated optimal lipid and glucose metabolism, while children on artificial or mixed feeding had higher triglycerides, LDL, and total cholesterol levels, as well as accelerated weight gain. Early nutritional interventions and proper care significantly reduce the risk of obesity and metabolic syndrome in later childhood.
Keywords: breastfeeding; infant feeding; metabolic disorders; lipid profile